If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + 3) + 12 = 13 + -6x Reorder the terms: -5(3 + x) + 12 = 13 + -6x (3 * -5 + x * -5) + 12 = 13 + -6x (-15 + -5x) + 12 = 13 + -6x Reorder the terms: -15 + 12 + -5x = 13 + -6x Combine like terms: -15 + 12 = -3 -3 + -5x = 13 + -6x Solving -3 + -5x = 13 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -3 + -5x + 6x = 13 + -6x + 6x Combine like terms: -5x + 6x = 1x -3 + 1x = 13 + -6x + 6x Combine like terms: -6x + 6x = 0 -3 + 1x = 13 + 0 -3 + 1x = 13 Add '3' to each side of the equation. -3 + 3 + 1x = 13 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = 13 + 3 1x = 13 + 3 Combine like terms: 13 + 3 = 16 1x = 16 Divide each side by '1'. x = 16 Simplifying x = 16
| 45=28+x | | 10x^3+14x^2-16x= | | 4(0.8g+1.5)=2(3+1.6) | | 3x-36=2x+14 | | s+4=3 | | (5a^3-5a+2)(a-4)= | | x-6.84=4.9 | | 5(x+3)+12=13-6x | | (3x+9)+(3x+8)+(3x)=(3x)+(3x)+(4x+5) | | K-7=-13-2k | | 4t+9=(-8)-13 | | 242=x+5-22 | | 405xy+245x^2= | | 6x+308= | | 5x+6x+2+2=3x+5+7x | | -9x-13+11x-25=2 | | (-10)7= | | f(x)=3e^5x | | 100-2P=40+2P | | 100-2P=40 | | log(x+5)=ln(x-3) | | m^2-5m+14=0 | | 5(2x-8)-7x=x+6 | | 40y^9+5y^4= | | 8x-3y+4=0 | | (-1)211= | | 12-m=2m | | 23=7x+3-2x | | y=4x+3x | | 48=x+9+2x | | .6x-.1=4 | | 0=5-n-7 |